Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's evaluate the summation [tex]\(\sum_{n=2}^7 \frac{(-1)^n(2n+1)}{3n-1}\)[/tex] step-by-step.
1. Identify the range of summation:
- The summation runs from [tex]\( n = 2 \)[/tex] to [tex]\( n = 7 \)[/tex].
2. Evaluate each term in the series:
- For [tex]\( n = 2 \)[/tex]:
[tex]\[ \frac{(-1)^2 (2 \cdot 2 + 1)}{3 \cdot 2 - 1} = \frac{1 \cdot 5}{6 - 1} = \frac{5}{5} = 1.0 \][/tex]
- For [tex]\( n = 3 \)[/tex]:
[tex]\[ \frac{(-1)^3 (2 \cdot 3 + 1)}{3 \cdot 3 - 1} = \frac{-1 \cdot 7}{9 - 1} = \frac{-7}{8} = -0.875 \][/tex]
- For [tex]\( n = 4 \)[/tex]:
[tex]\[ \frac{(-1)^4 (2 \cdot 4 + 1)}{3 \cdot 4 - 1} = \frac{1 \cdot 9}{12 - 1} = \frac{9}{11} \approx 0.8181818181818182 \][/tex]
- For [tex]\( n = 5 \)[/tex]:
[tex]\[ \frac{(-1)^5 (2 \cdot 5 + 1)}{3 \cdot 5 - 1} = \frac{-1 \cdot 11}{15 - 1} = \frac{-11}{14} \approx -0.7857142857142857 \][/tex]
- For [tex]\( n = 6 \)[/tex]:
[tex]\[ \frac{(-1)^6 (2 \cdot 6 + 1)}{3 \cdot 6 - 1} = \frac{1 \cdot 13}{18 - 1} = \frac{13}{17} \approx 0.7647058823529411 \][/tex]
- For [tex]\( n = 7 \)[/tex]:
[tex]\[ \frac{(-1)^7 (2 \cdot 7 + 1)}{3 \cdot 7 - 1} = \frac{-1 \cdot 15}{21 - 1} = \frac{-15}{20} = -0.75 \][/tex]
3. Sum the evaluated terms:
- The terms computed in the series are: [tex]\( 1.0, -0.875, 0.8181818181818182, -0.7857142857142857, 0.7647058823529411, -0.75 \)[/tex].
- Adding these together:
[tex]\[ 1.0 + (-0.875) + 0.8181818181818182 + (-0.7857142857142857) + 0.7647058823529411 + (-0.75) \approx 0.17217341482047366 \][/tex]
Therefore, the sum of the series [tex]\(\sum_{n=2}^7 \frac{(-1)^n(2n+1)}{3n-1}\)[/tex] is approximately [tex]\(0.17217341482047366\)[/tex].
1. Identify the range of summation:
- The summation runs from [tex]\( n = 2 \)[/tex] to [tex]\( n = 7 \)[/tex].
2. Evaluate each term in the series:
- For [tex]\( n = 2 \)[/tex]:
[tex]\[ \frac{(-1)^2 (2 \cdot 2 + 1)}{3 \cdot 2 - 1} = \frac{1 \cdot 5}{6 - 1} = \frac{5}{5} = 1.0 \][/tex]
- For [tex]\( n = 3 \)[/tex]:
[tex]\[ \frac{(-1)^3 (2 \cdot 3 + 1)}{3 \cdot 3 - 1} = \frac{-1 \cdot 7}{9 - 1} = \frac{-7}{8} = -0.875 \][/tex]
- For [tex]\( n = 4 \)[/tex]:
[tex]\[ \frac{(-1)^4 (2 \cdot 4 + 1)}{3 \cdot 4 - 1} = \frac{1 \cdot 9}{12 - 1} = \frac{9}{11} \approx 0.8181818181818182 \][/tex]
- For [tex]\( n = 5 \)[/tex]:
[tex]\[ \frac{(-1)^5 (2 \cdot 5 + 1)}{3 \cdot 5 - 1} = \frac{-1 \cdot 11}{15 - 1} = \frac{-11}{14} \approx -0.7857142857142857 \][/tex]
- For [tex]\( n = 6 \)[/tex]:
[tex]\[ \frac{(-1)^6 (2 \cdot 6 + 1)}{3 \cdot 6 - 1} = \frac{1 \cdot 13}{18 - 1} = \frac{13}{17} \approx 0.7647058823529411 \][/tex]
- For [tex]\( n = 7 \)[/tex]:
[tex]\[ \frac{(-1)^7 (2 \cdot 7 + 1)}{3 \cdot 7 - 1} = \frac{-1 \cdot 15}{21 - 1} = \frac{-15}{20} = -0.75 \][/tex]
3. Sum the evaluated terms:
- The terms computed in the series are: [tex]\( 1.0, -0.875, 0.8181818181818182, -0.7857142857142857, 0.7647058823529411, -0.75 \)[/tex].
- Adding these together:
[tex]\[ 1.0 + (-0.875) + 0.8181818181818182 + (-0.7857142857142857) + 0.7647058823529411 + (-0.75) \approx 0.17217341482047366 \][/tex]
Therefore, the sum of the series [tex]\(\sum_{n=2}^7 \frac{(-1)^n(2n+1)}{3n-1}\)[/tex] is approximately [tex]\(0.17217341482047366\)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.